Dimensions of Institutional Technologies and Its Role in Convergence of Sustainable Supply Chain Management and International Marketing: Systematic Literature Review - Muhammad Nafees Khan; Zhen Shao (Systems)
The convergence of International Marketing (IM) and Sustainable Supply Chain Management (SSCM) with the help of Institutional Technologies (IT) can be an important tool in the transformation of global business models. However, there is a clear gap in the current literature regarding the role of technology, organization, and environment (TOE) in this integration. In particular, it is unclear how these aspects of institutional technologies enable or impede integration and how the capabilities of enterprises change as a result. To fill this gap, this research describes the role of TOE aspects through a systematic literature review (SLR) of 40 analyzed papers. We used a subjective analysis of secondary data to show that technology modernization, organizational flexibility, and environmental policies are key drivers of integration, while technology incompatibility and limited information-sharing capabilities create barriers to the process. We present a conceptual framework that clarifies the stages of integration and propose 12 questions for future research. The results suggest that moderators should focus on the synergies between TOE aspects to develop effective integration strategies. This research provides a theoretical foundation for understanding the bilateral relationship between institutional technologies and integration, helping to create sustainable global business models.